Blank Spots Identification on Plantations - Crulhas, J. P. R. [UNESP]; Artero, A. O. [UNESP]; Piteri, M. A. [UNESP]; Silva, F. A.; Pereira, D. R.; Eler, D. M. [UNESP]; Papa, J. P. [UNESP]; Albuquerque, V. H. C. de (Ieee-inst Electrical Electronics Engineers Inc, 2018)
This paper presents a proposal to make the identification of failures in plantations performing an automatic analysis of images collected by the UAVs. What is sought is to identify and measure the areas where the process of seed germination did not occur as expected and then assist in taking a decision to maintain the current planting, or in the case of large areas with this problem, redoing the entire sowing process, avoiding production losses. The results obtained with some synthetic and real images are also quite satisfactory, showing the feasibility of the proposal, identifying the areas where failures occur and also measuring the areas of the regions identified.
Keywords: Computer Vision; Image Analysis; Segmentation Precision Agriculture; UAVs